2020
DOI: 10.1039/c9ce01533g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in transition metal based compound catalysts for water splitting from the perspective of crystal engineering

Abstract: A review of the recent progress on the transition metal based catalysts for water splitting with emphasis on crystal engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…In recent years, various transition metal (TM) phosphides, 10 oxides, 11 chalcogenides, 12 borides, 13 nitrides 14 and their composites 15 have emerged as effective OER catalysts. Among these cost-efficient catalysts, TM phosphides are regarded as catalysts with superior electrocatalytic activity and stability in alkaline media to effectively promote the OER process in terms of thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various transition metal (TM) phosphides, 10 oxides, 11 chalcogenides, 12 borides, 13 nitrides 14 and their composites 15 have emerged as effective OER catalysts. Among these cost-efficient catalysts, TM phosphides are regarded as catalysts with superior electrocatalytic activity and stability in alkaline media to effectively promote the OER process in terms of thermodynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the surface area and concentration of active sites, fabrication of amorphous metal oxides catalysts have recently gained increased attention . Amorphous metal oxides have shown superior electrocatalytic activity compared to their crystalline counterpart.…”
Section: Figurementioning
confidence: 99%
“…Amorphous materials have the unique advantages of long‐range disorder and isotropy [32] . Many dangling bonds in the amorphous phase increase the surface energy, which is generally beneficial for the adsorption of the reaction intermediate [33] . The presence of a large proportion of the coordination with unsaturated atoms in the amorphous phase can introduce a large number of defects that can provide active sites for catalysis, [34] thus improving the reaction kinetics of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a large proportion of the coordination with unsaturated atoms in the amorphous phase can introduce a large number of defects that can provide active sites for catalysis, [34] thus improving the reaction kinetics of catalysts. However, pure amorphous catalysts increase the space resistance of the electron transport due to dangling bonds, and their conductivity is worse than that of corresponding crystalline catalysts [33] . Experimental and theoretical calculation studies have shown that partially amorphous catalysts have more OER catalytic potential than pure amorphous or crystalline catalysts [35–36] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation